New control scheme for a dynamic voltage restorer based on selective harmonic injection technique with repetitive controller - Tapre, Pawan C.; Thakre, Mohan P.; Pawase, Ramesh S.; Thorat, Jaywant S.; Dahigaonkar, Dipak J.; Mapari, Rahul G.; Kadlag, Sunil Somnath; Khule, Shridhar (Institute of Advanced Engineering and Science, 2024)
Repetitive controller and selective harmonic injection technique (SHI) in medium and low voltage distribution networks improve dynamic voltage restorer (DVR) DC bus voltages as well as nullify power quality (PQ) problems. DVRs use sinusoidal pulse width modulation (SPWM) firing control, but DC bus use seems to be limited, affecting density, cost, and power packaging. By adding 1/6th of the 3rd harmonic waveform to the basic waveform, SPWM yields the developed model. According to the findings, 15% of DC bus usage improves and produces high voltage AC. Nevertheless, just control systems perturb PQ. The proposed controller uses feed forward and feedback to enhance transient response and justify stable zero error. 3rd third harmonic injection pulse width modulation (THIPWM) improves total harmonic distortion (THD) in the proposed scheme. Power system computer aided design (PSCAD) simulation produced high accuracy for THIPWM and repetitive controllers.